(untitled) (International Journal of Studies in Nursing, 2017)
Introduction: Based on Duffy’s (2009) Quality Caring Model and Hill and Watson’s Caring Science Curriculum Model (2011), the School of Nursing embraces the philosophy that caring collaborative relationships are the center of a culture of quality caring in nursing. Culture and cultural competence are integral to caring. Immersion experiences have been identified as impacting cultural competence (Bentley & Ellison, 2007; Kohlbry, 2016; Larsen & Reif, 2011; Long, 2012). Methodology: This paper describes the planning, implementation and lessons learned from an immersion experience as part of a mission focused study abroad course to Quito, Ecuador. Discussion: Twelve students, three faculty, and two nurse practitioners cared for approximately 100 patients per day for 10 days. Lessons learned related to faculty, students and logistics are discussed. Results: Students demonstrated positive outcomes related to critical thinking and clinical reasoning, holistic care of diverse populations, communication and collaboration, professional accountability, and effective teaching strategies.